Improving Elementary School Student Learning Outcomes Through Teacher Professional Development - Badara, Aris; Marwati, Marwati; Sulfiah, Sulfiah (International Journal of Educational Research Excellence (IJERE), 2024)
This research aims to explore improving elementary school student learning outcomes through teacher professional development. The research method used is lesson study, where teachers collaborate to design, implement and evaluate lessons on an ongoing basis. The research was conducted by collecting data from elementary school students who implemented lesson study for one semester. The research results showed that there was a significant increase in student learning outcomes after implementing teacher professional development through lesson study. Data analysis shows consistent improvements in student learning outcomes. Apart from that, it was also found that students were more active and involved in the learning process, and were better able to apply the concepts they learned in the context of everyday life. The conclusion of this research is that teacher professional development through lesson study has a significant positive impact on student learning outcomes in elementary schools. Collaboration between teachers in designing and evaluating learning helps increase the effectiveness of teaching and learning. It also emphasizes the importance of continuous professional development for teachers in improving the quality of education.